Wilms tumor presenting as small bowel obstruction in a neonate: A diagnostic challenge - Selim Ahmed; Chandran Nadarajan; Chiak Yot Ng; Yong Guang Teh; Muhammad Zahid Abdul Muien; Constance Sat Lin (Elsevier Inc, 2021)
Wilms tumor is the most common primary malignant renal tumor of childhood which usually presents between 2 and 6 years of age. Its presentation in the neonatal period is ex- tremely rare and presenting with intestinal obstruction is perhaps unknown. We report a 2- day-old baby girl who manifested features of acute upper gastrointestinal obstruction with frequent post-feeding vomiting and abdominal distension. The initial abdominal radiograph showed abnormally displayed small bowel loops to the right hemiabdomen. Subsequent ultrasound and computed tomography scan of the abdomen detected a massive left renal mass. Left-sided nephrectomy was performed, and histopathology demonstrated left-sided Wilms tumor with favorable histology. Post-treatment yearly follow-up for 5 years recorded a disease-free, normally thriving child.